Development of assessment instruments 4C skills (critical thinking, collaboration, communication, and creativity) on parabolic motion materials - Rudianto Rudianto; Rahma Diani; Subandi Subandi; Nanda Widiawati (Journal of Advanced Sciences and Mathematics Education, 2022)
4C skills are one of the abilities in life that can produce knowledge personally and be used in society. This study aimed to develop an instrument for assessing students' 4C skills (Critical Thinking, Collaboration, Communication, and Creativity) on parabolic motion material. The model used in developing this research is the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection methods were interviews, questionnaires, tests, and documentation with a population of 120 students and a sample of 60 students. The sample selection technique uses cluster random sampling. Based on the study results, the percentage of critical thinking criteria was 21.7 percent, low critical thinking was 28.3 percent, and poor critical thinking was 50 percent. The percentages with creative thinking criteria are 25 percent, 40 percent moderately creative, and 35 percent less creative. The percentage of collaboration skills that meet excellent criteria is 65 percent, and high collaboration skills are 35 percent. While the percentage of people with excellent communication skills was 8.3 percent, high communication skill was 83.3 percent, and fairly high communication skill was 8.3 percent. Based on these data, it concluded that the instruments developed were valid and feasible to use.